Law Transformation in The Field of International Trade Contract into Indonesian Positive Law - David Tan (Universitas Internasional Batam, 2019)
International trade is very influential to economic growth which then influences national welfare and development. This is similar to the idea of a welfare state. Economic rights are also guaranteed by the Indonesian state constitution. On the other hand, international state communities have produced many international legal products that regulate international trade, for example the UNIDROIT Principles of International Commercial Contracts (UPICC), United Nations Convention on Contracts for the International Sale of Goods (CISG) and International Commercial Terms (INCOTERMS). This research was conducted to determine the process of legal transformation into Indonesian positive law. This research is a study from a legal political perspective, because it tries to transform the ius constituendum into ius constitutum. The legal theory used is the Convergence Law Theory to explain the symptoms of legal convergence with the aim of achieving economic efficiency. This research uses juridical normative research. Data sources used are sourced from primary, secondary and tertiary legal data. Data finding is done using library research. Data are then analyzed qualitatively in order to classify the aspects studied. Then, conclusions related to this study were drawn and then described descriptively.